FAKTOR PENYEBAB IRREGULARITIES PENANGANAN OPERASIONAL PESAWAT MEDICAL EVACUATION DI BANDARA HALIM PERDANAKUSUMA - Sari, Mustika (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
This research aimed to analyze the causes of irregularities on airplane medical evacuation (medevac) handling and find the solution and effective action. Method used in this research is fishbone. The results show that there are 13 factors causes the irregularities which are the age of GSE is over 20 years old, the Medevac Standard Operating Procedure (SOP), briefing and debriefing activity, documentation, diesel fuel, spare part, office utility, employees’ recruitment, career path, training, operational cost, salary increases, and bonus. The solutions are that at the beginning of recruitment the company should tell the new employee about the employment status, periodic increment, and training, for the company fuel storage, the company should socialize the rules of work safety by conducting safety campaign program periodically, for documentation, it is better for the operation administrator to document and jot down all operational activities, meanwhile for the night-shift employee should be changed with different people, for the spare part, there should be some spare stored in GSE warehouse, about the SOP, the company should make special SOP for medevac activities, office utility should be updated with the newest technology, and for GSE equipment, there should be budget to buy new GSE equipment